(untitled) (Praxis Educativa, 2021)
This articles shares and problematizes a series of narrative compositions produced in pandemic times. Within the framework of the Project “The construction of Teacher Subjectivities in the Teacher Education Programs: narratives and (other) practices at the University and the Teacher Education Colleges in Mar del Plata” carried out by the Research Program on Educational Settings and Subjectivities (GIESE) at the School of Humanities, University of Mar del Plata, Argentina, we have committed ourselves to listening to and identifying what may trigger us to imagine other ways of inhabiting university institutions. Moving towards the poetics of drama, this work also explores different pedagogical lenses for interpretation and embraces the power of narrative research in order to re-imagine and re-create our educational experiences. Keywords: University Education; Narrative Research; Pedagogical Turn; COVID pandemic